McDonald´s inc- leading the QSR industry at all velocity - Ramos, Gonçalo Da Silva (2020)
After the former CEO exit and quarterly disappointing results, McDonald’s stock went down 10.7% of its all-time high of $221.93 (Aug19). We provide an in-depth DCF valuation an a lys is explaining the main assumptions behind our BUY recommendation. We propose a price-target of $225.91,mainly driven by the re-franchising success–that is boosting operating margin;and by same-store sales –which have been benefiting from further implementations of the Velocity Growth Plan. Moreover,we looked further to strategy, share holders and capital’s structure, making sure that McDonald’s comparables we reconsidered in order to provide a relative valuation and benchmark our DCF valuation.